Comparing Genetic Value of Bulls from Different Breeds: Across Breed EPDs - Gary R. Hansen (EDIS)
AN162, a 5-page fact sheet by Gary R. Hansen, describes how to use tables developed by the US Meat Animal Research Center (MARC) which provide adjustment factors to allow for the calculation of across-breed expected progeny differences (AB-EPDs) to assess genetic potential across different breeds. Published by the UF Department of Animal Science, March 2006.